EDUCATIONAL REFLECTIONS OF A NOVICE TEACHER IN A PHILIPPINE PRIVATE SCHOOL - Louie Giray (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
In this manuscript, the researcher aimed to understand his lived experiences, beliefs, and the culture he is in, being a novice grade school teacher in a Philippine private school. Reflection as a research methodology is utilized to make sense of the data generated. The discussion is thematically dived into three parts, namely—(1) the delivery of instruction; (2) school and classroom culture; and (3) the school community. This paper contends that reflection fosters active thought about actions and situations, making the teacher truly engaged in the course of education. Reflection can help strive toward learning and progress. It is suggested for teachers to intentionally reflect so as to invite continuous learning and progress. This especially can be a manifestation of authenticity in the business of facilitation of learning among teachers. Furthermore, reflection is a prerequisite to rethinking pedagogical styles and teaching craft, leading to innovation in the educational arena.